STRATEGI BISNIS DALAM MENINGKATKAN KINERJA BADAN USAHA MILIK DAERAH (BUMD) DI PROVINSI JAMBI - Fitriaty Fitriaty (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
The Local Enterprises is one of the enterprises established by local governments and the aim is to implementation regional development through service to the community, organizing public benefit and increase local revenue (PAD). For that enterprises must have good business performance.The Management is expected to increase of uniqueness resources and implementation on competitive strategies and partnerships to take advantage of business opportunities for impact on business performance improvement. This study purposed on measuring the effect of market attractiveness, uniqueness of resources,and partnerships and its implications on business performance. research object is owned companies in Jambi Province. The unit of analysis is the management of local enterprise managers and business unit heads. The research shows that the enterprises in Jambi Province, in improving business performance need to do a strategic relationship with stakeholders and to design competitive strategy . The dimensions of forming the uniqueness resources is tangible assets followed intangible assets.